A Cross-Sectional Survey of Pakistani Muslims Coping with Health Anxiety through Religiosity during the COVID-19 Pandemic - Mahmood, Qaisar Khalid (J Relig Health, 2021)
Investigating the role of religiosity in coping with health anxiety during the outbreak of COVID-19 assumes significance given the continued onslaught of the pandemic and the importance of religion in many societies of the world. The aim of this study is to test the relationship between religious coping and health anxiety in Pakistani Muslims. The online survey method was used to collect data from 408 respondents. Structural equational modeling was performed, with results indicating that people who are suffering with health anxiety opt for religious coping (β = .54, R(2) = .29, p < .001). We conclude that it is important to consider the role of religion and spirituality during pandemic-induced anxiety. There are implications for counselors, physicians and researchers to integrate religious coping methods when planning mental health interventions during pandemics and otherwise.